Effect of instructing mothers on their performance in relation to the application of pit and fissure sealants in 6-8 year-old children in Isfahan - Faezeh Eslamipour; Fatemeh Zabihi (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: Considering the positive effect of health education on behavior change and health promotion, this study aimed at evaluating the effect of an educational program about fissure sealant therapy (FST) on behavior of mothers in relation to providing FST for their children.Materials and Methods: This randomized controlled trial evaluated 180 students with an age range of 6 to 9 years and their mothers in Isfahan. The participants were randomly divided to 3 groups: 2 intervention and one control group. The subjects were included if they had at least one sound first molar and excluded if they had any history of FST. One intervention group received the educational program through an oral presentation supplemented with a pamphlet and the other group was mailed only a pamphlet. The control group did not receive any instruction. After three months, the subjects' first molars were clinically examined for the presence of FST. Descriptive analysis and chi-squared test were used for data analysis at 95% confidence interval.Results: After three months, 11.7% of the subjects had FSTs, 66% of which were in the oral presentation group and 34% were in the pamphlet group. There were no teeth with FST in the control group. There were no significant differences between the intervention groups (p value < 0.08); however, there were significant differences between the intervention groups and the control group (p value = 0.001).Conclusion: Educational programs can effectively change the attitudes of mothers and encourage them to provide fissure sealant services for their children.Key words: Behavior, Education, Pit and fissure sealants, Prevention.